Development of ginseng powder using high hydrostatic pressure treatment combined with UV-TiO2 photocatalysis - Hyunah Lee; Hafiz Muhammad Shahbaz; Namho Ha; Jeong Un Kim; Sang Jun Lee; Jiyong Park (Journal of Ginseng Research, 2020)
Background: Korean ginseng (Panax ginseng Meyer) powder is in rising demand because powder forms of foods are convenient to handle and are highly preservable. However, ginseng powder (GP) manufactured using the conventional process of air drying and dry milling suffers nutrient destruction and a lack of microbiological safety. The objective of this study was to prepare GP using a novel process comprised of UV-TiO2 photocatalysis (UVTP) as a prewashing step, wet grinding, high hydrostatic pressure (HHP), and freeze-drying treatments. Methods: The effects of UVTP and HHP treatments on the microbial population, ginsenoside concentration, and physiological characteristics of GP were evaluated. Results: When UVTP for 10 min and HHP at 600 MPa for 5 min were combined, initial 4.95 log CFU/g-fw counts of total aerobes in fresh ginseng were reduced to lower than the detection limit. The levels of 7 major ginsenosides in UVTP-HHP–treated GP were significantly higher than in untreated control samples. Stronger inhibitory effects against inflammatory mediator production and antioxidant activity were observed in UVTP-HHP–treated GP than in untreated samples. There were also no significant differences in CIELAB color values of UVTP-HHP–treated GP compared with untreated control samples. Conclusion: Combined processing of UVTP and HHP increased ginsenoside levels and enhanced the microbiological safety and physiological activity of GP. Keywords: Ginseng powder, Ginsenoside, High hydrostatic pressure, Microbiological safety, Physiological activity